Prevalence of Indian Culture over Western Culture in 21st Century - Shah, Pratima; Agrawal, Saumya; Joby, Juliya; Ansari, Sania; Bhandari, Rutvi; Bhatt, Isha (Integrated Journal for Research in Arts and Humanities, 2023)
Indian culture is not only one of the oldest and richest cultures in the world, but also serves as a base for the development of other cultures time and again. On the other hand, western culture is considered as one of the contemporary yet most advanced cultures that is influencing various other cultures across the globe. In this world of technological advancement, intermixing of various cultures is not new. Infact, it helps one adopt the positives of multiple cultures. But sometimes it becomes slightly far-fetched when one starts comparing and disregarding their own culture. A similar situation can be observed in India. Many complain about the influence of western culture over Indians to a great extent, especially in the 21st century, based on what is visible. But one needs to understand that it is just the tip of an iceberg, a superficial observation. The influence of any situation is determined by its impact on the psychology of a person. The following research conducted gives a deeper insight on the same. Roots are the beliefs, and customs of the family and culture that are carried on from generation to generation. Some rituals considered as ancient superstitions turn out to have actual benefits. For generations things were handed down from Father to Son, and Mother to Daughter. Hence, parents wish for their kids to be grounded to their cultural/familial roots. Though the changes are prevalent in various domains, such as political, social, economic, industrial and technological, the new generation still stick to their roots and prefer living in a joint family while celebrating Indian culture compared to western culture.